Bay Leaf Extract Aggravated Fungal Infections in The Rat Model of Oral Candidiasis. - Sulistyani, Erna; Triwahyuni, Iin Eliana; Dewi, Leni Rokhma; Futaihana, Hasna' Garaniva; Andriani, Hilma; Agustin, Merry Ayu Ayu; Khairunnisa, Luthfitah Zahra (Odonto : Dental Journal, 2025)
Background: The prevalence of oral candidiasis has been increasing in recent years due to various factors, such as diseases that weaken the immune system, medication, xerostomia, and chemotherapy. The types of antifungal drugs are still very limited, and those that can be given systemically have significant side effects. Numerous in-vitro studies have demonstrated that bay leaves have antifungal properties. This study aimed to evaluate the effect of bay leaf extract in vivo on the oral candidiasis rat model.Method: The rat model for oral candidiasis was created by adding Tetracycline HCl 500 mg/L to the rats' drinking water. Then, the rats were injected with methylprednisolone one day before and after inoculating 0.3 ml of Candida albicans (9.4 x 107 cells/ml) into the oral cavity of the rats. The bay leaf extract was given to two groups of the oral candidiasis rat model by intragastric tube at 250 mg/kgBW/day (P1) and 500 mg/kgBW/day (P2)  doses for 5 days.  Oral candidiasis infection was evaluated on the last day by counting the number of colonies from swabs of the oral mucosa cultured on SDA-C. Result: After 5 days of treatment, the number of fungal colonies of group P2 was surprisingly higher than P1, positive and negative control. Conclusion: This study revealed that bay leaf extract aggravated oral candidiasis in vivo. The flavonoids in bay leaves may inhibit the production of pro-inflammatory cytokines, which could diminish the rats' immune response.